Potential roles of oxidative distress on neurodegeneration in Parkinson's disease with neuropsychiatric symptoms - Li, Dan-ning; Lian, Teng-hong; Zhang, Wei-Jiao; Zhang, Ya-nan; Guo, Peng; Guan, Hui-ying; Li, Jing-hui; He, Ming-yue; Zhang, Wen-jing; Zhang, Wei-jia; Luo, Dong-mei; Wang, Xiao-min; et al. (Frontiers in Aging Neuroscience, 2022)
Background Neuropsychiatric symptoms (NPSs) belong to a category of non-motor symptoms of Parkinson's disease (PD), which seriously compromise the quality of life and prognosis of PD. This study focused on the correlations between NPSs, free radicals, neuroinflammatory factors, and neuropathological proteins in cerebrospinal fluid (CSF) in patients with PD, aiming to provide insights into the potential mechanisms and therapeutic target for PD with NPSs (PD-NPSs). Methods In total, 129 patients with PD were enrolled and assessed by the Neuropsychiatric Symptoms Inventory (NPI); they were divided into the PD-NPSs group (75 patients) and PD with no NPSs (PD-nNPSs) group (54 patients). The levels of hydrogen peroxide (H2O2) and nitric oxide (NO), and hydroxyl radical (·OH), anti-oxidative enzyme, neuroinflammatory factors, and neuropathological proteins in CSF from patients with PD were measured. The levels of the above variables were compared between PD-NPSs and PD-nNPSs groups, and correlation analyses among the above variables were conducted. Results (1) The levels of H2O2 and NO in CSF from the PD-NPSs group were significantly elevated compared with the PD-nNPSs group (p = 0.001), and NPI score positively correlated with the levels of H2O2 and NO (r = 0.283, P = 0.001; r = 0.231, P = 0.008). Reversely, total superoxide dismutase (tSOD) activity in CSF from the PD-NPSs group was significantly reduced compared with the PD-nNPSs group (p = 0.011), and negatively correlated with NPI score (r = −0.185, p = 0.036). (2) The tumor necrosis factor (TNF)-α level in CSF from the PD-NPSs group was significantly decreased compared with the PD-nNPSs group (p = 0.002) and negatively correlated with NPI score (r = −0.211, p = 0.016). (3) The total tau (T-tau) level in CSF from the PD-NPSs group was significantly higher than in the PD-nNPSs group (p = 0.014) and positively correlated with the NPI score (r = 0.167, p = 0.060). (4) The levels of H2O2 and NO positively correlated with the T-tau level in CSF from the PD-NPSs group (r = 0.183, p = 0.039; r = 0.251, P = 0.004), and the levels of TNF-α and T-tau showed a negative correlation (r = −0.163, p = 0.067). Conclusion Oxidative distress characterized by the elevations of H2O2 and NO levels may closely correlate with the neurodegeneration in brain regions related to PD-NPSs. Thus, therapeutic antioxidants may become an important target for PD-NPSs therapy.